Dampak pandemi covid-19 terhadap keluhan kesehatan siswa sekolah dasar negeri di jawa barat - Beltasar Tarigan; Teten Hidayat (Journal Of Sport Education (JOPE), 2022)
The study aimed to analyze the direct effects of the COVID-19 pandemic on the health complaints of elementary school children across West Java. In addition, the specific aim of this study was to obtain empirical evidence on student health complaints during the Covid-19 pandemic. The research method of this study was to use self-made and validated instruments. Data analysis using Microsoft Excel and SPSS 24. The population in this study was elementary school students in West Java. For this study, the number of samples used was adjusted to match elementary school students across West Java drawn at simple random so that 1,867 students were offset. In this study, an instrument in the form of a questionnaire is used and then the data is checked against a Likert scale. The results showed: The students' health complaints during the Covid-19 pandemic were as follows: hypokinetic illness or sedentary lifestyle (60%), decreased physical fitness (60%), decreased immunity (60%), weight gain (62%), Feeling fatter (57%), sleeping irregularly (44%), slightly tired (15%), weak and less energetic (16%), heartburn (8%), frequent dizziness (7%), getting sick easily (flu) ) (14%). Other effects experienced by students include decreased immunity, decreased physical fitness, decreased cardiovascular ability, and frequent injuriesCopyright © The Author (s) 2022Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.